Vaginal birth in singleton breech:revisited - Chaudhari, Hemangi K.; Tiruke, Raviraj D.; Shah, Parmanand K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The purpose of the study was to analyze maternal and perinatal outcome according to mode of delivery in singleton breech presentation retrospectively in a tertiary care center. Methods: This was a retrospective observational study done in KEM Hospital, during 2012 to 2013. Maternal and perinatal outcome was studied retrospectively. The data was collected from the mother’s medical records. The neonatology records were also examined. Primary outcomes included neonatal mortality, morbidity and maternal morbidity. Results: Out of 100 selected patients; 27 delivered vaginally and 73 underwent lower segment caesarean section (LSCS). Perinatal mortality was 3%. Two out of 3 were delivered vaginally and 1 underwent LSCS. Perinatal morbidity was 1% in vaginal delivery. Maternal morbidity was 2%, both patients underwent emergency LSCS. There was no maternal mortality in the study. Conclusions: Delivery of breech fetus when labor and delivery is supervised and or conducted by experienced obstetrician lowers maternal morbidity, neonatal morbidity and mortality.